Sports and Exercise Therapy in Holistic Strategy for Treating Chronic Diseases – literature review - Bieńko, Mateusz; Rutkowska, Marta; Król, Tomasz; Toborek, Michalina; Marchaj, Magdalena; Korta, Karolina; Putra, Anna; Niedziela, Natalia; Margas, Mikołaj (Journal of Education, Health and Sport, 2024)
Introduction The convergence of sports and health is a developing area, focusing on the therapeutic potential of physical activities in numerous chronic disease management strategies as a necessary part of a holistic strategy. Acknowledging sports as a therapeutic tool emphasizes the necessity for a comprehensive understanding of how sports engagement contributes to innovative healthcare interventions. Purpose This research aims to investigate the therapeutic potential of prescribing sports and physical exercise in treating primary chronic diseases, exploring its integration into healthcare practices with a focus on efficacy and implications for disease management. State of Knowledge Physical activity is recommended for treating diabetes, chronic obstructive pulmonary disease, asthma, and rheumatoid arthritis. It reduces the risk of cardiovascular disease and death, lowers blood pressure, ads prevents and manages atherosclerosis and osteoporosis. Non-physical sports like chess and board games also promise protection against dementia, depression, and Alzheimer’s. Conclusions Incorporating sports into healthcare policies and prescribing personalized exercise are essential components of holistic chronic disease management and show widespread benefits. Professional guidance and clear recommendations, aligned with disease-specific guidelines, play a crucial role in ensuring safe and effective physical activity for patients. Potential risks in specific populations, particularly injury risks, can be minimized through proper preventive measures, adjusting the character of exercises, and heightened patient awareness. To ensure good compliance, exercise prescriptions should offer clear and precise guidelines.